Influence of anthropometric measures and socio-demographic factors on menstrual pain and irregular menstrual cycles among university students in Bangladesh - Hossain, M.G.; Sabiruzzaman, M.; Islam, S.; Hisyam, R.Z.; Lestrel, P.E.; Kamarul, Tunku (2011)
Menstrual disturbances generally affect the daily activities of young females. The aim of this study was to determine the effects of anthropometric measures and sociodemographic factors on menstrual disturbances among university students in Bangladesh. Data were collected from 995 students from Rajshahi University using a stratified sampling technique between July 2004 and May 2005. Factors influencing menstrual pain and irregular menstrual cycles were examined with multiple logistic regression analysis. Stepwise logistic regression analysis was also used to determine the most influential factors affecting menstrual disturbances. The prevalence of menstrual pain among the university students studied was very high (72.3), while the experience of irregular menstrual cycles was very low (12.9). Multiple logistic regressions demonstrated that menstrual pain was affected by early age at menarche, early birth order, longer length of menstrual flow and high family income. Students suffering from irregular menstrual cycles displayed a delay in menarche, longer duration of menstrual flow and larger body mass index (BMI) values. Moreover, stepwise logistic regression showed that age at menarche, birth order, duration of menstrual flow and family income were the most important factors influencing menstrual pain. Age at menarche, duration of menstrual flow and BM I were found to be the most important factors affecting irregular menstrual cycles. These results suggest that age at menarche and duration of menstrual flow are significant common factors which affect menstrual pain and irregular menstrual cycles. Consequently, menstrual disturbance can be considered as one of the major health problems of Bangladeshi university female students and requires attention.